Reformulating Indonesia’s Development Paradigm toward Sustainable Prosperity - Ayu Angelina Pasaribu; Herry Daniel Laurent Marpaung (Universitas Negeri Semarang, 2026)
This study reexamines Indonesia’s development paradigm with a focus on achieving sustainable welfare. Employing a dynamic panel data approach, the analysis investigates the effects of social, economic, and environmental dimensions on sustainable welfare proxied by the Gini ratio across 34 provinces over the 2019–2024 period. To address endogeneity concerns and capture dynamic relationships, the Generalized Method of Moments (GMM) is applied. The estimation results from the FDGMM, SYSGMM, and DPGMM models satisfy the criteria of validity, consistency, and unbiasedness. Overall, the findings indicate that the explanatory variables in all three models exert a strong, negative, and statistically significant effect on inequality reduction, thereby enhancing sustainable welfare. However, per capita income exhibits a positive yet statistically insignificant impact on welfare in both the short and long run. Based on these findings, the study recommends a reformulation of Indonesia’s development paradigm toward sustainable welfare by positioning the Human Development Index (HDI) as the core foundation of development and structural reform. The results underscore the need for policy innovation that prioritizes HDI-based development, accelerates structural transformation, and promotes green job creation. Ultimately, progressive, inclusive, and consistent policy design is essential for achieving sustainable wellbeing, with a strong emphasis on equity and long-term sustainability